Neuroinflammation and Autism - Wang, Qing M.; Luo, Andrew Z.; Kong, Xuejun (North American Journal of Medicine and Science, 2014)
The incidence of autism spectrum disorder (ASD) has increased significantly in the past decades, now affecting 1 out of 68 children in USA. The complexity of this disorder and the unclear mechanisms have hindered the development of an effective therapeutic regimen. Recent studies have suggested that neuro-inflammation plays an important role in the pathogenesis of ASD. A literature review was conducted to examine the evidence of various central immune processes involved in ASD. Conventional and novel medications for ASD treatment were summarized.